HYBRID OPTIMIZATION METHOD OF CONTINUUM STRUCTURE AND ITS SUPPORTING LOCATIONS - HU TianNan; DING XiaoHong (Jixie qiangdu)
In engineering problems,there is interaction between the layout of supporting locations and the distribution of structural material. Thus,simultaneously optimizing the topology of the structure and its supporting locations under a certain limit of material and supports is an effective approach to improve the mechanical properties of the structure. In this paper,supporting locations are described by continuous variables with the introduction of the independent supporting elements,then a hybrid optimization method of continuum structure and its supporting locations is proposed. The mathematical models of multi-objective optimization are established considering both the structural stiffness and the mean eigenvalue of the structure. The optimal solution of multi-objective optimization is determined by a certain decision factor. A simply supported plate under bending and bending-torsion loading conditions are optimized by the proposed hybrid optimization method. The results show that the distribution of material and supporting locations is clear,and the layout of supporting locations and the topology of structure can be effectively optimized at the same time. Compared with the design results from the standard topology optimization with given supporting conditions,the static and dynamic performances of the two examples are improved more than 30% and 88%,respectively. It is found that the proposed design method can satisfy the constraints,and remarkably improve the static and dynamic performance of the structure with a smaller number of supporters.